Pitiriasis Rosea: Manifestasi Klinis Dan Tatalaksana - Akbar Hanardi, Muhammad; Rizki Ardhan, Faris; Vidyadevi Wiguna, Visakha; Thasliyah, Dhila; Putu Yunandari, Ni (Jurnal Syntax Fusion, 2022)
Pitiriasis rosea (PR) is a papulosquamous disorder with appearance of multiple, discrete patchesof skin rash in a distinctive pattern over the trunk and limbs. Epidemiologic studies on PR in Africa showed 2,2% to 4,8% dermatologist patient have a PR. The incidence is 170 cases per 100,000 persons per year and It typically affects persons 10 to 35 years of age. The clinical presentation of PR can be a single larger lesion, measuring about 2 to 10 centimetres, usually precedes the widespread rash for up to two weeks. This initial lesion, also known as the 'herald patch', most commonly appears on the trunk, and then the secondary eruption occurs. Lesions are similar to the herald patch but smaller. Their distribution commonly follows the skin cleavage lines in what is referred to as the 'Christmas tree pattern'. The risk factor of PR such as COVID-19 infection, herpes virus reactivation, environmental factors, and pregnancy factors. Treatment is aimed at controlling symptoms and consists of antihistamines, antibiotics or corticosteroids. In some cases, acyclovir can be used to treat symptoms and reduce the length of disease. Ultraviolet phototherapy can also be considered for severe cases